Keefektifan Konseling Kelompok REBT untuk Meningkatkan Self Esteem Mahasiswa - Eva Kartika Wulan Sari; Laily Tiarani Soejanto (JKI (Jurnal Konseling Indonesia), 2016)
Specifically, this research aims to know the effectiveness of REBT Group Counseling to improve the self-esteem of college students. The subjects in this research were students of the faculty of science education force in 2015 identified as having the characteristics of low self esteem. The population in this research is 742 people consisting of 5 courses. A sample of members of the population use purposive sampling techniques. The research instrument used treatment material in the form of the implementation guidelines REBT group counseling and self-esteem scale that Rosenberg's self-esteem scale which has proven validity and reliability. The conclusion in this research is 1) There is an increase in self-esteem from 100% of college students have low self-esteem after being given the results obtained REBT group counseling 40% of college students in the moderate category and 60% in the high category. 2) Self-esteem increased after the college students is given REBT group counseling or could mean that the effective group counseling to improve the self-esteem of college students.The suggestion in this research is: 1) The suggestions for counseling and testing centers that REBT group counseling can be used as an help for students in problem solving. 2) The suggestion for further researcher is for further research in order to apply the techniques that are diverse in the REBT group counseling.